DEVELOPMENT OF ACADEMIC COMMUNICATION SKILLS: METHODS OF WORK ORGANIZATION - V. V. Levchenko; E. V. Agrikova; M A. Voronina (Высшее образование в России)
The article reflects the experience of the work organization that is aimed at development of academic communication skills at Samara University. The authors highlighted and described the necessary pedagogic conditions that were applied by creation of Samara Academic Consultancy Center based on Modern Languages and Professional Communication department, Samara University. The authors paid special attention to the mission of the center, its objectives, and principles of work and activity of the organization. Moreover, the article shows the schedule of academic skills development for each university level (bachelors, masters, postgraduate students and teaching staff) that was developed by the tutors of Samara Academic Consultancy Center.